2021
DOI: 10.1016/j.brs.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Polarity-specific high-definition transcranial direct current stimulation of the anterior and posterior default mode network improves remote memory retrieval

Abstract: Background: Previous studies show that activity in the posterior default mode network (pDMN), including the posterior cingulate cortex and the precuneus, is correlated with the success of long-term episodic memory retrieval. However, the role of the anterior DMN (aDMN) including the medial prefrontal cortex is still unclear. Some studies show that activating the medial prefrontal cortex improves memory retrieval while other studies show deactivation of the medial prefrontal cortex in successful retrieval of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…However, the positioning of the return electrode/s was highly inconsistent, resulting in a diverse set of montages used in the experiments. Moreover, a few studies targeted other brain areas, including the temporal cortex (e.g., [ 28 ]) and occipital nerve [ 58 ], or used unique montages targeting various brain areas at once [ 54 ]. Some versions of standard AM tasks (source memory and tasks where participants had to pair words and/or pictures) were used in all papers, along with standard outcome measures of cued recall (19 studies) or recognition (14 studies).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the positioning of the return electrode/s was highly inconsistent, resulting in a diverse set of montages used in the experiments. Moreover, a few studies targeted other brain areas, including the temporal cortex (e.g., [ 28 ]) and occipital nerve [ 58 ], or used unique montages targeting various brain areas at once [ 54 ]. Some versions of standard AM tasks (source memory and tasks where participants had to pair words and/or pictures) were used in all papers, along with standard outcome measures of cued recall (19 studies) or recognition (14 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, 18 out of 29 studies found positive tES effects on AM, 7 studies presented evidence of tES decreasing AM performance, while 4 studies reported null effects on all AM outcomes. There is no apparent relationship between the AM effects and the type of tES protocol applied, as positive effects were reported following anodal tDCS [ 32 , 33 , 44 , 47 , 49 , 52 , 53 , 57 ], tACS [ 58 , 59 ], otDCS [ 52 , 59 ], HD-tDCS [ 54 ], HD-tACS [ 48 ] and even cathodal tDCS [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many studies run the models on the example head included with ROAST or an individual sample from the investigators. These work cover various clinical applications including: attention-deficit hyperactivity disorder [ 61 , 62 ], aging [ 63 ], associative memory [ 64 , 65 ], attention [ 66 – 68 ], body awareness [ 69 ], cognitive control and function [ 70 ]; Fusco et al [ 125 ]; [ 71 , 72 ], connectivity [ 73 ], decision making [ 74 77 ]; Schulreich and Schwabe [ 126 ], declarative learning [ 78 ], depressive disorder [ 79 ], electroencephalography (EEG) research [ 80 83 ], imitation [ 84 ], memory retrieval [ 85 87 ], mind wandering [ 88 , 89 ], motor learning [ 90 95 ], motor skills [ 96 98 ], neurorehabilitation [ 60 ], neurovascular coupling [ 99 ], obsessive-compulsive disorder [ 100 ], phantom limb pain [ 101 ], post-anoxic leukoencephalopathy [ 102 ], reading speed [ 103 ], schizophrenia [ 104 ], social anxiety disorder [ 105 ], stroke [ 106 ], visual perception [ 107 , 108 ], and working memory [ 109 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our final dataset consists of 63 participants’ data, with 21 in the left-anode group ( M age = 20.4, SD = 1.17), 20 in the right-anode group ( M age = 19.7, SD = 1.22), and 22 in the sham group (11 left-sham and 11 right-sham, M age = 20.6, SD = 3.27). We considered this sample size acceptable given that similar or smaller sample sizes have been used in prior studies investigating tDCS modulation of memory (Huang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%